2022
DOI: 10.1155/2022/3639352
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Available Intervention Strategies for Postural Balance Control in Individuals with Autism Spectrum Disorder

Abstract: Background. Postural instability is a prevalent issue among individuals with autism spectrum disorder (ASD) that affects the development of their perceptual-motor skills and social functioning. Visual and somatosensory processing deficits, hypotonia, basal ganglia dysfunction, and anxiety are some of the concurrent disorders in individuals with ASD. Nevertheless, a definite management protocol for postural instability in ASD has not been introduced yet. Hence, we aim to shed light on the available intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Moreover, the postural balance improvements identified in this study must be viewed cautiously, as they reflect short-term effects. The study by Hariri et al [25] underlines the importance of examining the retention of these skills over an extended period to ensure the long-term efficacy of such interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the postural balance improvements identified in this study must be viewed cautiously, as they reflect short-term effects. The study by Hariri et al [25] underlines the importance of examining the retention of these skills over an extended period to ensure the long-term efficacy of such interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Motor symptoms such as tiptoeing can reduce balance and stamina in children with ASD, increasing the likelihood of falls and leading to more significant fatigue and less participation in social activities, which can negatively impact daily activities such as play, sports, and walking [7][8][9][10][11][12][13][14]. Although traditional treatments have provided moderate improvements in ASD-related behaviors, exercise and physical activities are being increasingly recognized as viable alternative treatments [23][24][25][26][27][28]. These treatments aim to enhance balance by stimulating the sensory systems, including the visual, vestibular, and proprioceptive systems, which have successfully improved joint proprioception and overall motor performance [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various SI therapies are currently used in clinical practice including swimming, trampolines, martial arts, transcranial direct current stimulation, animal-assisted therapies such as riding, sports, dance, videogames, as well as specific balance training exercises. It has been found that these therapies can enhance an individual’s sensory input integration processes, motor skills and coordination, and cerebellar function, which all help to improve balance control [ 63 ]. SI therapy testing can also be used as a diagnostic tool for clinicians in the early detection of ASD and vestibular dysfunction; however, auditory dysfunction is sometimes wrongly attributed to other neurodevelopmental disorders [ 64 ].…”
Section: Balance and Vestibular Dysfunctionmentioning
confidence: 99%
“…Although results are not conclusive, they have been encouraging with sensory stimulation interventions (Sam et al, 2017), visual feedback through video games (Travers et al, 2018;Hilton et al, 2014;Somogyi et al, 2016;Peña et al, 2020), gymnastic and neuromuscular training (Akyol & Pektas, 2018;Najafabadi et al, 2018;Shavikloo & Norasteh, 2018), therapeutic skating (Casey et al, 2015), Tai Chi Chuan (Sarabzadeh et al, 2019), and also with the help of elephants (Nuntanee & Daranee, 2019) and horses (Portela-Pino et al, 2019). Hariri et al (2022), in a systematic review of the literature, shed light on the available intervention strategies for improving postural control in people with ASD. This study has reported that most interventions affect motor function in ASD by improving cerebellar or balance function, integration and processing of sensory information, muscle strength and correction of body alignment.…”
Section: Balance Improvement Interventionsmentioning
confidence: 99%